PEMBUATAN GAME ANDROID TOWER DEFENSE “MYTH OF JAVA” - Hendaryie Hendaryie; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
This game was designed using Unity Game Engine and is targeted to Android smartphone. Aseprite is used to design the sprite in this game. There are 8 stages in this game. Each stage has a different level of difficulty. The aim of this game is to destroy the opponent's tower while protecting the player's tower from being destroyed by the opponent’s. The win condition is when the opponent's tower has destroyed. Testing is done by blackbox testing, alpha testing by the supervisor, and beta testing through a survey of 40 respondents. The test results show that “Myth of Java” is a game that is quite interesting. This is because “Myth of Java” has several stages with different levels of difficulties. It also has a background story that takes from the mystical beliefs that exist in Java Island.